Isolasi dan identifikasi senyawa golongan flavonoid dari kelopak bunga rosella (Hibiscus sabdariffa, Linn) menggunakan metode sonikasi - Azzahra, Syafira (Maliki Interdisciplinary Journal, 2023)
Rosella flower is a plant that contains anthocyanins. Anthocyanins are included in the flavonoid compound which has a conjugated double bond system that functions as an antioxidant. The purpose of this study was to determine how to isolate flavonoid compounds, the results of phytochemical tests, and the characterization of rosella (Hibiscuss sabdariffa, Linn) flower flavonoids using a UV-Vis spectrophotometer, FTIR, GC-MS, and 1HNMR. The method used is the sonication method. The extraction results using the sonication method obtained a red concentrated extract with a yield of 37.57% from 25 grams of rosella. The result of the hydrolysis process is the formation of CO2 bubbles with side products in the form of H2O and NaCl salt. The result of the partition process is the formation of 2 layers, namely the organic phase and the water phase with a yield of 14.61%. In this study, the results of the solution were orange (brownish orange) indicating a positive result for flavonoids through a phytochemical test. KLTP monitoring results are in the form of yellow spots with Rf 0.7125. The results of characterization using UV-Vis obtained a wavelength of 268.9 nm. The results of the FTIR obtained some typical absorption of functional groups from flavonoids. The results of the GC-MS characterization obtained a peak with a retention time of 20.377 which is the peak of the flavonoid compound.